A educação permanente em saúde na organização da politica nacional de humanização na atenção básica - Lopes, Maria Tereza Soares Rezende (2016)
This study aimed to analyze the practices of Permanent Education in Health that permeated the processes of implementation and organization of the National Humanization Policy in basic care. It was a research made through a qualitative approach, of the exploratory and descriptive type. For that, a focal group technique was used, with workers from six Basic Health Units from a municipality in the northwest of the State of Paraná-Brazil. The transcripts were submitted to the thematic content analysis technique proposed by Bardin, with the aid of six word clouds generated by the IRAMUTEQ software. These clouds provided the definition of categories, which were: Category 1- The National Humanization Policy devices brought positive changes to the work processes and were mediated by practices of Permanent Education in Health; Category 2 - The Permanent Education in Health that guided the implementation of the guidelines and devices of the National Humanization Policy was marked by collective practices and protagonists; Category 3 - The collective work permeated by learning was a reality in the implementation of the devices of the National Humanization Policy; Category 4 - The collaborative support of the team and the knowledge sharing are scenarios that allow learning and transformation; And Category 5- Work meetings and informal team conversations are scenarios that concretize the permanent evaluation of the implementation of the National Humanization Policy and provide opportunities for learning and transformation. The data were discussed by the light of Paulo Freire's reference, regarding the questioning in the production of knowledge and practices. The research was conducted by following the current ethical precepts and the authorization of the competent body of the Municipal Health Department. This study demonstrated that many guidelines and devices of the Humanization Policy were implemented in the units and this implementation was conducted by permanent education practices. The National Policies of Permanent Education in Health and Humanization have positively influenced the teams' work processes. It was verified that, in the studied scenario, despite all obstacles, the practices of permanent education have permeated the work processes for the implementation of the guidelines and devices of the National Humanization Policy.